Technological Transformation in the Global Pulp and Paper Industry 1800-2018 Comparative Perspectives (World Forests,, 2018)
This contributed volume provides 11 illustrative case studies of technological transformation in the global pulp and paper industry from the inception of mechanical papermaking in early nineteenth century Europe until its recent developments in today's business environment with rapidly changing market dynamics and consumer behaviour. It deals with the relationships between technology transfer, technology leadership, raw material dependence, and product variety on a global scale. The study itemises the main drivers in technology transfer that affected this process, including the availability of technology, knowledge, investments and raw materials on the one hand, and demand characteristics on the other hand, within regional, national and transnational organisational frameworks. The volume is intended as a basic introduction to the history of papermaking technology, and it is aimed at students and teachers as course material and as a handbook for professionals working in either industry, research centres or universities. It caters to graduate audiences in forestry, business, technical sciences, and history.